2023
DOI: 10.3389/fpsyg.2023.1009639
|View full text |Cite
|
Sign up to set email alerts
|

Impact of authentic leadership on employee turnover intention: Perceived supervisor support as mediator and organizational identification as moderator

Abstract: Authentic leadership is considered a critical factor for retaining talented employees. However, despite fruitful findings, researchers have paid little attention to how authentic leadership is associated with employee turnover intention. Drawing on organizational support theory, justice literature, and social identity theory, we examine the effects of supervisors’ authentic leadership on employee turnover intention to better understand how authentic leaders reduce employees’ turnover intention in Asian context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 125 publications
(201 reference statements)
0
0
0
Order By: Relevance
“…This result was consistent with prior research suggesting that higher levels of family support among employees decreased the probability of turnover (Aulia & Haerani, 2023;Shrestha et al, 2019;Le, 2020). Furthermore, with regard to past empirical studies, the findings in this study also correspond to those reported by Jun et al (2023); Ilyas et al (2020), indicating that there is a significant interaction between care and the supervisor support in relation to turnover intention, and higher levels of supervisor support are associated with lower turnover intentions. There is a reciprocal relationship between the support from the work domains and family.…”
Section: Discussionsupporting
confidence: 88%
“…This result was consistent with prior research suggesting that higher levels of family support among employees decreased the probability of turnover (Aulia & Haerani, 2023;Shrestha et al, 2019;Le, 2020). Furthermore, with regard to past empirical studies, the findings in this study also correspond to those reported by Jun et al (2023); Ilyas et al (2020), indicating that there is a significant interaction between care and the supervisor support in relation to turnover intention, and higher levels of supervisor support are associated with lower turnover intentions. There is a reciprocal relationship between the support from the work domains and family.…”
Section: Discussionsupporting
confidence: 88%
“…This prompts researchers to explore factors influencing employees' TI, involving aspects related to employees, jobs, and organizations. Employee factors include demographic characteristics and personal factors such as age, gender, tenure, work values, and family reasons; job factors involve job characteristics and workload; organizational factors encompass organization size, culture, and HRM Practices (Jun et al, 2023;Xu et al, 2023;Chami-Malaeb, 2022). These factors directly or indirectly influence employees' TI, thereby affecting organizational stability and performance.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies in the past have identified different reasons influencing turnover (Hancock et al, 2013). Through a review of over 300 studies, work stress, management style, managerial support, and individual factors such as age, tenure, number of children, education level, and career development have been identified as crucial factors affecting turnover (Jun et al, 2023;Park and Min, 2020). These factors can be categorized into three aspects: employee, job, and organizational (Chami-Malaeb, 2022).…”
Section: Previous Study On Ti As a Dependent Variablementioning
confidence: 99%
See 1 more Smart Citation
“…This approach has piqued the curiosity of organizational scholars and practitioners alike [2], resulting in two focal avenues in contemporary research. The first highlights the range of effects authentic leadership has on followers, spanning diverse outcomes, such as job satisfaction, organizational citizenship behavior (OCB), job performance, and work engagement [3][4][5][6][7]. The second stream is devoted to understanding the fundamental processes by which authentic leadership impacts these outcomes at both individual and organizational levels [8].…”
Section: Introductionmentioning
confidence: 99%